Mekanisme Penundaan Keputusan Tata Usaha Negara dalam Sengketa Tata Usaha Negara Ditinjau dari Prinsip Perlindungan Hukum (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This research aims to examine the postponement mechanism in State Administrative Court (TUN) disputes, particularly the legal basis and practice of determining postponements by panels of judges, and to formulate an ideal mechanism for postponement requests based on the principles of legal protection. This study employs a qualitative method with a normative juridical legal research approach, involving the analysis of legal concepts, normative structures, comparisons of legal norms, and the legal implications of regulations. The research analyzes regulations governing the postponement of State Administrative Decisions (KTUN) under the State Administrative Court Law (Law No. 5 of 1986, Law No. 9 of 2004, and Law No. 51 of 2009) and the Government Administration Law. The existing regulatory framework reflects normative stagnation, as it has not been substantially revised through the amendments to the PTUN Law. The current mechanism remains rigid and restrictive, particularly due to the requirement of “extremely urgent circumstances,” which is open to multiple interpretations and difficult to prove, as well as the absence of provisions on sanctions and execution supervision. An ideal mechanism requires progressive, rapid, flexible, and balanced procedural reform based on three pillars: substantive criteria reform, procedural law reform, and execution and supervision reform.